Clean Energy Transition and Intertemporal Socio-Economic Development: A Case Study of Households in Indonesia - Satrio Arga Effendi (Publikasi Indonesia, 2024)
The use of polluting energy sources for daily household needs can lead to complex issues, ranging from health deterioration and reduced quality of life to adverse socioeconomic consequences. While previous studies have predominantly focused on the health and welfare impacts of dirty energy use, this research highlights the effects of clean energy transition on household socioeconomic development, employing an innovative approach through the Household Development Index (HHDI). This longitudinal study utilizes data from the Indonesian Family Life Survey (IFLS) conducted in 2007 and 2014, revealing the dynamics of household energy consumption changes over a seven-year period. The study employs the Propensity Score Matching (PSM) method to calculate the average treatment effect on the treated of household clean energy transition. The analysis results show that households transitioning to cleaner energy sources experienced a 3.72% higher increase in development index compared to if they had continued using unclean energy. Robustness tests were conducted using the Coarsened Exact Matching (CEM) technique and a combination of CEM-PSM. These robustness tests also yielded similar and consistent results. Impact estimations performed on different sub-samples indicate that the impact of energy transition in rural areas is greater than in urban areas. This research makes an important contribution by presenting new empirical evidence on the comprehensive impact of clean energy transition on household socio-economic development.